Fundamentalisme Islam: Kecenderungan antara Menafsirkan Realitas dan Doktrin - Aden Wizjan SZ (Unisia, 2002)
The article below tries to describe the position of the fundamentalism of  Islam as the trend between understanding the realities of religion followers and interpreting the doctrine of religion. Actually the term " fundamentalism " is not discovered as .a particular term in Moslem society. The term is emerged in the Western society, especially in the context of the Protestant Christian in the United States of America. Historically, it appears closely relation with the role of religion facing the development of the liberalization, the modernization and, the secularization. The result of the involving causes community of western countries to place the religion institutions face knowledge, but, in this sense it becomes the diametyral enemy. At the same time, the Western colonialism against the under-developing countries and the social scientists of humanism, and orientalists introduce the term fundamentalism to their colonized people. According to them that the Islamic States or Moslem countries in the term of colonization have similarities experiences as those of theirs. Really it is stated that the phenomena of fundamentalism have similarities generally but there are some differences in the context of their particularities